Using Data Envelopment Analysis to Measure the Technical Efficiency of Public Hospitals in Turkey - Karahan, Mehmet (Ege Univ, Fac Economics & Admin Sciences, 2019)
In the study, it was targeted to increase the efficiency of business by identifying the performance and efficiency levels of 1533 public hospitals in 81 provinces of Turkey by means of data envelopment analysis and, in addition to this, identifying the problems of units causing disruptions; it was aimed to sort out these problems by suggesting solutions. The data obtained from health businesses, in which application was performed, were checked; their efficiency degrees were assessed; and analysis results were obtained. These results obtained from the study were used in the improvement studies that are going to be carried out to increase the efficiency of or remove the deficiencies of hospitals, in which application is performed. According to the results obtained, the technical efficiencies of 1533 businesses being active in 81 provinces and presenting similar health services were measured by means of data envelopment analysis and it was identified that 775 of these hospitals that are present in 36 provinces worked efficiently, and that 758 of them that are present in 45 provinces did not work efficiently.
Keywords: Data envelopment; efficiency analysis; hospital efficiency; health businesses